2010
DOI: 10.4049/jimmunol.1001374
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Is an Essential Regulator of T Cell Activation Competence in Uterine Dendritic Cells during Early Pregnancy in Mice

Abstract: Uterine dendritic cells (DCs) are critical for activating the T cell response mediating maternal immune tolerance of the semiallogeneicfetus. GM-CSF (CSF2), a known regulator of DCs, is synthesized by uterine epithelial cells during induction of tolerance in early pregnancy. To investigate the role of GM-CSF in regulating uterine DCs and macrophages, Csf2-null mutant and wild-type mice were evaluated at estrus, and in the periconceptual and peri-implantation periods. Immunohistochemistry showed no effect of GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 70 publications
1
47
1
2
Order By: Relevance
“…Null mutation and cytokine add-back experiments in mice show that seminal fluid-induced cytokine synthesis in reproductive tract epithelial cells is the first step in the female response to seminal fluid and occurs upstream of inflammatory leukocyte recruitment (43)(44)(45). The data reported in this study are consistent with seminal plasma-induced cytokines acting to control leukocyte recruitment and activation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Null mutation and cytokine add-back experiments in mice show that seminal fluid-induced cytokine synthesis in reproductive tract epithelial cells is the first step in the female response to seminal fluid and occurs upstream of inflammatory leukocyte recruitment (43)(44)(45). The data reported in this study are consistent with seminal plasma-induced cytokines acting to control leukocyte recruitment and activation.…”
Section: Discussionsupporting
confidence: 80%
“…A third and potentially critical function for the macrophages and DCs recruited into the cervical stroma and epithelium after coitus is to activate immune responses to sperm and microbial Ags contained within the ejaculate. The increase in APCs induced by seminal fluid in the human cervix is reminiscent of findings in mice and pigs, where macrophages and DCs expressing MHCII, scavenger receptor, and other activation markers invade the uterine endometrium and en- gulf ejaculate material after mating (4,7,45,57). Studies in mice show that these cells have a key function in cross-presenting seminal fluid Ags to activate cognate T cells (13).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the numbers of uterine macrophages are not altered in GM-CSF-deficient mice (Moldenhauer et al, 2010), which contrasts data from M-CSF-deficient mice where uterine macrophages are almost absent (Wiktor-Jedrzejczak and Gordon, 1996).…”
Section: The Influence Of M-csf and Il-10 On Decidual Macrophage Polacontrasting
confidence: 47%
“…20,21 Athanassakis et al 22 has been showed that granulocyte-macrophage colony stimulating factor (GM-CSF) was also important in pregnancy. This has been followed by the work of Robertson and her colleagues 23 who have shown GM-CSF is not only important in the female, but its production in sperm can also be necessary. Various other studies have been well documented that cytokines and chemokines play a vital role in human pregnancy.…”
Section: Pregnancy Endocrine-like Peptidesmentioning
confidence: 99%